Določanje odzivne površine z optimalnim statističnim cenilnikom - Prošek, Andrej (Strojniški vestnik, 2000)
In the field of nuclear ingineering the response surface is used to solve some problems related to nuclear safety. The main purpose of the study was to develop a tool suitable for response surface generation of complex and non-linear phenomena and to demonstrate its applicability for the response surface generation of peak clsdding temperature during a small-break loss-of-coolant accident in a nuclear power plant. The optimal statistical estimator, adapted for use in multi dimensional space, was used for response surface generation. For assessing the adequacy and predictive capability of the optimal statistical estimator two statistics were built in, and the possibility to set the width of the Gaussian curve. The performance of the optimal statistical estimator was tested with the results from 59 different calculations of the small-break loss-of-coolant accident. The applicationof the optimal statistical estimator shows several advantages when compared to the more commonly used regression analysis. The results showed that the response surface for the peak cladding temperature was adequately predicted bythe optimal statistical estimator but not with regression analysis. Furthermore, an ability to automate the response surface generation provides the possibility of using the optimal statistical estimator for an uncertainty evaluation of any kind of time dependent phenomena and transients.
Keywords: površine odzivne; optimalni statistični cenilec; najvišja temperatura srajčke; varnost jedrska; odzivna površina; jedrska varnost; temperatura; optimiranje